Turkish validity and reliability of the Self-Report Instrument to Measure Patient Safety Attitudes, Skills, and Knowledge - Nuray Turan; Seçil Erden Melikoğlu; Zühal Nas (BMC, 2024)
Abstract Aims The present study was carried out methodologically to provide the Turkish equivalence of the Self-Report Instrument to Measure Patient Safety Attitudes, Skills, and Knowledge and to determine its reliability and validity. Methods This methodological study included 317 nurses. The back-translation method was used to test the linguistic equivalence of the methodological scale. Experts' opinions were asked to test its content validity. Time invariance (test-retest reliability) and internal consistency were tested to test its reliability. A group of 100 nurses participated in the test-retest. The content validity index and confirmatory factor analysis were used to test its validity. Results The scale was highly reliable, with a content validity index value of 0.965 and an overall internal consistency coefficient of 0.875. Confirmatory Factor Anaysis (CFA) showed that the goodness-of-fit indices were good and that the model was suitable for this situation. Conclusions The Turkish version of this scale is reliable and valid for evaluating nurses' knowledge and attitudes about patient safety and their perceptions of patient safety culture. Therefore, it is possible to apply this approach in studies carried out in Türkiye.